Enhanced voltage endurance capability of Ba(Zr0.2Ti0.8)O3 thin films induced by atomic-layer-deposited Al2O3 intercalations and the application in electrostatic energy storage. Issue 6 (15th March 2021) - Mao, Niefang; Meng, Linghao; Li, Yawei; Hu, Zhigao; Chu, Junhao
Abstract: Ultrathin Al2 O3 insulating intercalations with different thicknesses and numbers, prepared by atomic layer deposition technology, were introduced into Ba(Zr0.2 Ti0.8 )O3 (BZT) relaxor ferroelectric films as the dielectric for electrostatic energy storage capacitors. The phase structure, microstructure and electrical properties were investigated in detail. Due to the insertion of insulating layers, the films show less leakage current and enhanced voltage endurance capability when the thickness of single Al2 O3 intercalation exceeds a threshold (0.45–0.9 nm). The voltage endurance capability can be more enhanced by increasing the number of Al2 O3 intercalations. For energy storage applications, the energy storage density and efficiency obtained from the polarization-electric field loops are significantly improved owing to the suppressed leakage and enhanced voltage endurance ability. The results promote the application of BZT-based films in electrostatic energy storage. It is demonstrated that the introduction of atomic-layer-deposited insulating intercalations with controllable thickness, such as those fabricated by ALD method, is an effective way to improve the electrical performance of devices based on composite materials.